Comportamiento agronómico del cultivo de arroz (Oryza sativa L.), aplicando micorrizas (Glomus sp), en suelos con problemas de salinidad, bajo condiciones de invernadero - Olvera Guerrero, Antonio Rafael (2019)
VIII. SUMMARY The present research work was carried out in the premises of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km. 7.5 of the Babahoyo-Montalvo road. The geographic coordinates (UTM) are X: 668690 E; Y:9801098 N. The zone presents a humid tropical climate, with an average temperature of 24 to 26 ° C, relative humidity 88%, annual precipitation of 1262 mm, a height of 8 msnm2 and 990 hours of annual average heliophany. Seeds of rice, variety INIAP 14 were used as seed material. The treatments consisted of different doses of mycorrhizae, such as: 0.5 and 1.0 l / ha; 10 and 20 kg / ha; plus a control treatment without application of the product. The experimental design Randomized with four treatments and 3 repetitions was used, the test of significance used was Tukey at 95% probability. All the necessary agricultural work in rice cultivation was carried out for its normal development as land preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvest. To estimate the effects of the treatments, the following data were taken: plant height, number of tillers, length and width of the flag leaf and leaf 2, number of panicles, length of panicles, grains per panicles, yield of grain per panicle, length of the root, weight of 1000 grains, length and width of the husked grain, vigor, days of flowering, yield of grain and economic analysis. Based on the results obtained, it was determined that the application of mycorrhizae obtained positive effects on the performance of the rice crop, variety INIAP 14; so the importance of applying mycorrhizas is reflected; agronomic characteristics such as plant height, tillers and panicles / m2, length of panicles, grains per spike, yield and economic analysis reached higher averages using mycorrhizae in doses of 10 kg / ha, with a net profit of $ 196.27